2011
DOI: 10.4028/www.scientific.net/amr.233-235.1332
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Correlation of Solubility for 2,4-Dinitrotoluent in Mixed Solvents of Water and Nitric Acid

Abstract: The solubility data of 2,4-dinitrotoluent (2,4-DNT) in mixed solvents of water and nitric acid with nitric acid mass fraction vary from 0.1 to 0.5 were determined at 283.15-323.15K by the equilibrium method. It indicates that the solubility increases with the increase of temperature and decreases with the decrease of mass fraction of nitric acid. The experimental data were correlated with λ-h equation, Apelblat equation and C.L.Yaws equation, average relative deviations of which between the calculated values a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…DNTs are known to be poorly soluble in aqueous media . Kong et al, however, reported that 2,4-DNT is more soluble in acidic solutions . 2,4-DNT was found to be more soluble in a solution of sulfuric acid where 200 ppm was dissolved as opposed to a 100 ppm limit typically reported for water.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNTs are known to be poorly soluble in aqueous media . Kong et al, however, reported that 2,4-DNT is more soluble in acidic solutions . 2,4-DNT was found to be more soluble in a solution of sulfuric acid where 200 ppm was dissolved as opposed to a 100 ppm limit typically reported for water.…”
Section: Resultsmentioning
confidence: 99%
“…This becomes critical, for example, when extracting DNT from soil samples, potentially alongside other analytes of interest. It has been reported by Kong et al, however, that acidic solutions improve the solubility of DNT, and sulfuric acid is reported to have a reasonable potential window . Thus, sulfuric acid was explored as a supporting acidic electrolyte in the current work.…”
Section: Introductionmentioning
confidence: 99%